“We were not up to the situation”: limits of citizen participation in the Espinar’s dialogue table (2012-2013) - De la Puente Burlando, Lorena (2019)
The dialogue table in Espinar is recognized as an emblematic case of dialogue processes. However, three barriers compromised the quality of representation of civil society: the overloading of urban leaders, the underrepresentation of peasant interests and the use of technical languages to regulate decision-making. The study of this case aims to explore the limits and contradictions of participatory processes after socio-environmental conflicts in Peru. The objective is to contribute to the revision of their methodologies and to question the ideas from which different stakeholders built their participation.